2018
DOI: 10.1371/journal.pone.0200547
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomic approach in men with carotid plaque

Abstract: BackgroundThe aim of the study was to analyse the presence of several metabolites related to atherosclerosis in the plasma of patients with unstable carotid plaque and in the plasma of healthy subjects.Materials and methodsWe included 20 patients who had undergone carotid endarterectomy and 20 healthy subjects as a control group. All the subjects recruited were male. We used a metabolomic approach with liquid chromatography coupled to mass spectrometry to evaluate plasma metabolite levels in the metabolic path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Recent studies have documented a role for 20-HETE in the pathogenesis of diabetes and obesity-related cardiovascular and metabolic disorders. These studies showed that 1) levels of 20-HETE are highly increased in individuals with obesity (BMI Ͼ30) and metabolic syndrome (1,17,28,32,36,37), as well as in animal models (8, 18, 30, 31); 2) polymorphism in the human 20-HETE synthase CYP4F2 is associated with metabolic syndrome phenotypes (6,11,35); 3) in vitro, 20-HETE induces hyperglycemia, impairs insulin signaling (21,23,39), and is adipogenic (20); and 4) increased 20-HETE levels in diabetic animals have been shown to contribute to diabetic nephropathy (2, 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have documented a role for 20-HETE in the pathogenesis of diabetes and obesity-related cardiovascular and metabolic disorders. These studies showed that 1) levels of 20-HETE are highly increased in individuals with obesity (BMI Ͼ30) and metabolic syndrome (1,17,28,32,36,37), as well as in animal models (8, 18, 30, 31); 2) polymorphism in the human 20-HETE synthase CYP4F2 is associated with metabolic syndrome phenotypes (6,11,35); 3) in vitro, 20-HETE induces hyperglycemia, impairs insulin signaling (21,23,39), and is adipogenic (20); and 4) increased 20-HETE levels in diabetic animals have been shown to contribute to diabetic nephropathy (2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Although much has been learned regarding the relationship between adiposity, metabolic disorders, and chronic disease, the exact underlying cellular and molecular mechanisms are yet to be fully explored. Recent studies in humans demonstrated a close direct relationship between body mass index and the urinary and/or plasma levels of 20-hydroxyeicoastetraenoic acid (20-HETE), a cytochrome P-450 (CYP) 4-derived arachidonic acid metabolite (1,17,28,32). 20-HETE was first characterized as a vasoactive eicosanoid that promotes vascular smooth muscle contraction, endothelial dysfunction, inflammation, and cell proliferation (10).…”
Section: Introductionmentioning
confidence: 99%
“…20-HETE synthase was elevated on the ipsilateral side 7 days after brain ischemic injury in a positron emission tomography (PET)-based study [62] suggesting upregulation of CYP4A and CYP4F isoforms might be involved in angiogenesis and neuroinflammation after stroke. Moreover, in a study analyzing carotid plaque characteristics, 20-HETE was found to be significantly higher in a patient with atheroma plaques compared to other metabolites [63]. Whether the 20-HETE content in the atheromatous plaque has any consequence on stroke outcome is still unclear, however, genetic variations in CYP450 isoforms have also been associated with plaque stability in patients with ischemic stroke [64].…”
Section: 20-hete In Strokementioning
confidence: 99%
“…Elevated concentrations of 5-HETE, 12-HETE, and 15-HETE were reported in individuals with acute cardiac syndrome ( 17 ). Elevated circulating concentrations of 5-HETE, 12-HETE, and 15-HETE were reported in individuals with CAD by Xu et al ( 20 ), whereas only numerical increases were reported by Shishebor et al ( 19 ) and Auguet et al ( 21 ); the latter did not quantify 5-HETE. The role of elevated mid-chain HETE in cardiovascular dysfunction has been well documented, whereas less is known of the role of mid-chain HODE ( 3 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 90%